Legislation of the byzantine emperors of the 8th — early 10th centuries on monks: traditions and innovations - Anna Vankova (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article studies the legislation on monks and monasteries of the Byzantine emperors of the 8th to the early 10th centuries. Most of the legal codes under consideration are revision of the corpus of Emperor Justinian I. Therefore, the study involved collecting the most complete set of all norms of the period, and determining what part of Justinian’s extensive legislation was included in the legal codes of this time, what exactly the compilers of the codes borrowed, what new they brought. The article is divided into two chapters, i.e. the sources and the related problems on the one hand and the legislative norms on the other have been considered separately. The chapter on legislative norms, in turn, was divided into a number of paragraphs: guardianship, admission of a slave to the monastery, management of property (church and private) by monks and clergy, collection of taxes by them, emphyteusis and rental of property, immunity, family law and family property, property issues and apocrisiaries, issues of the internal life of the monastery and penal articles about the abduction of nuns, and the last paragraph is devoted to the norms of Basilica absent in other legal corps. Using the comparative historical method, the author has come to the following conclusions. The norms about monks and monasteries were collected as completely as possible in the secular legislation of the 8th to the early 10th centuries. It is in the “Basilica” that the norms of Justinian’s legislation received the most detailed consideration. Only a few norms were included in the Ecloga. At the same time, in the Basilica the vast majority of legal provisions were given without abbreviations. Of the entire Justinian corpus, the Novellas were used most; much less so materials from the Codex. Almost all major categories of laws related to monasticism were represented in the legislation of the Macedonian dynasty. Nevertheless, some provisions in the codes of the period were innovations, for example, the provision on guardianship in the Ecloga of Isaurian dynasty. The most innovative, as one would expect, is the collection of Novellas by Emperor Leo VI, while in a number of points the Novellas contradict the provisions of the “Basilica”. To establish the reasons for this, further study of the topic is required.